2019
DOI: 10.1242/jeb.201038
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of two Δ12-desaturases demonstrates targeted production of linoleic acid as pheromone precursor inNasonia

Abstract: Insect pheromones are often derived from fatty acid metabolism. Fatty acid desaturases, enzymes introducing double bonds into fatty acids, are crucial for the biosynthesis of these chemical signals. Δ12-desaturases catalyse the biosynthesis of linoleic acid by introducing a second double bond into oleic acid, but have been identified in only a few animal species. Here, we report the functional characterisation of two Δ12-desaturases, Nvit_D12a and Nvit_D12b, from the parasitic wasp Nasonia vitripennis. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…We demonstrated that the sex pheromone of N. giraulti males is produced from linoleic acid. This result confirms previous studies with the congeneric species N. vitripennis [52,53] and demonstrates that acetone application is a suitable and convenient tool to study biosynthetic pathways.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…We demonstrated that the sex pheromone of N. giraulti males is produced from linoleic acid. This result confirms previous studies with the congeneric species N. vitripennis [52,53] and demonstrates that acetone application is a suitable and convenient tool to study biosynthetic pathways.…”
Section: Plos Onesupporting
confidence: 91%
“…Both lactones are derived from fatty acid metabolism. 13 C labeling experiments have revealed that linoleic acid is a key intermediate in the pheromone biosynthesis of N. vitripennis while the other Nasonia species have not yet been studied in this respect [52][53][54]. Another aspect of the pheromone biosynthesis in Nasonia that has not yet been studied is the role of insect hormones such as juvenile hormone (JH) and 20-hydroxyecdysone (20-OH-E) which have been found to trigger pheromone biosynthesis in several other insect taxa [13,14,17,[55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…In samples from Ld, Ac, Ct, Hh, Te, and Nv, the respective isotope clusters were also detectable in the methyl esters of the unsaturated fatty acids oleic acid and linoleic acid (Figs. S4, S5 in the supplementary material) demonstrating that 13 C-labeled stearic acid had been processed by Δ9- and Δ12-desaturares [37].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on the pheromone biosynthesis revealed that Nv has a 12-desaturase enabling them to synthesize LA from oleic acid (OA; Blaul et al, 2014;Semmelmann et al, 2019b; see Figure 3). Wang et al (2015) found a predicted desaturase gene Nasvi2EG017727 to be 800-fold higher expressed in Nv males while a highly similar paralogue was expressed unbiasedly in both males and females.…”
Section: Biosynthesis Of the Male Marking Pheromonementioning
confidence: 99%
“…that both have in fact 12-desaturase activity. However, only Nvit_D12a was found to be expressed in the male pheromone gland suggesting that it acquired a specialized function in Nv for the production of LA as a pheromone precursor (Semmelmann et al, 2019b). The fact that Nv males are capable of synthesizing LA by themselves challenged the postulated importance of LA as a limited resource.…”
Section: Biosynthesis Of the Male Marking Pheromonementioning
confidence: 99%